Clinical utility of the 21-gene assay in predicting response to neoadjuvant endocrine therapy in breast cancer: A systematic review and meta-analysis - M.G. Davey; É.J. Ryan; M.R. Boland; M.K. Barry; A.J. Lowery; M.J. Kerin (Breast, 2021)
Introduction: OncotypeDX© Recurrence Score (RS) is a multigene panel used to aid therapeutic decision making in early-stage, estrogen receptor positive (ER+)/human epidermal growth factor receptor-2 negative (HER2-) breast cancer. Aim: To compare responses to neoadjuvant endocrine therapy (NET) in patients with ER+/HER2-breast cancer following substratification by RS testing. Methods: This systematic review was performed in accordance to the PRISMA guidelines. Studies evaluating pathological complete response (pCR), partial response (PR), and successful conversion to breast conservation surgery (BCS) rates following NET guided by RS were retrieved. Dichotomous outcomes were reported as odds ratios (ORs) with 95% confidence intervals (CIs) following estimation by Mantel-Haenszel method. Results: Eight prospective studies involving 691 patients were included. The mean age was 62.6 years (range 25–85) and the mean RS was 14.5 (range 0–68). Patients with RS < 25 (OR: 4.60, 95% CI: 2.53–8.37, P < 0.001) and RS < 30 (OR: 3.40, 95% CI: 1.96–5.91, P < 0.001) were more likely to achieve PR than their counterparts. NET prescription failed to increase BCS conversion rates for patients with RS < 18 (OR: 0.23, 95% CI: 0.04–1.47, P = 0.120) and RS > 30 (OR: 1.27, 95% CI: 0.64–2.49, P = 0.490) respectively. Only 22 patients achieved pCR (2.8%) and RS group failed to predict pCR following NET (P = 0.850). Conclusion: Estimations from this analysis indicate that those with low-intermediate RS on core biopsy are four times more likely to respond to NET than those with high-risk RS. Performing RS testing on diagnostic biopsy may be useful in guiding NET prescription.